Environmental genotoxicity and cytotoxicity studies in fish blood erythrocytes and genotoxicity risk assessment in the Gotland Basin of the Baltic Sea - Pažusienė, Janina (Institutional Repository of Vilnius University)
This thesis aims to assess the peculiarities of genotoxicity and cytotoxicity effects in fish species inhabiting the southern and eastern parts of the Gotland Basin of the Baltic Sea. In situ and in vivo studies results revealed cytogenetic effects on aquatic species caused by anthropogenic chemical and physical pollution. For the first time, genotoxicity and cytotoxicity levels were assessed in peripheral blood erythrocytes of herring (Clupea harengus membras), flounder (Platichtys flesus) and cod (Gadus morhua callarias) inhabiting the chemical weapons (CW) dumping site located in the eastern part of the Gotland Basin. The highest genotoxicity level was recorded in herring from the CW dumping zone. Exceptionally high and high genotoxicity risks to herring and flounder were determined at most the study stations located in the CW dumping zone and its vicinity. In situ studies provide new data about the ecological status of the southern part of the Gotland basin. Exceptionally high and high genotoxicity risks were found to herring, flounder and cod at all the study stations located in the oil and gas platform zone. According to the obtained genotoxicity risk results, the southern part of the Gotland basin cannot be qualified for the Good Environmental Status. For the first time the potential in vivo genotoxic and cytotoxic effects of 50 Hz 1 mT electromagnetic field (EMF) were assessed in rainbow trout (Oncorhynchus mykiss) larvae and Baltic clam (Limecola balthica). These findings suggest that exposure to the EMF of the intensity typically generated by submarine cables significantly negatively affects molluscs and early life stages of typical salmonids.